Religious Counseling: Dzikir untuk Mengatasi Kecemasan tentang Kematian Pasca Kecelakaan - Nulhusni, Nadyya; Prasetia, Agung; Wihanda, Deassy (Institut Agama Islam Negeri Kerinci, Indonesia, 2021)
Every individual must have experienced anxiety, both originating from within the individual and from outside the individual self. If anxiety is excessive, it is very bad for an individual's body, especially after an accident. Nowadays there are phenomena that occur in him that cause anxiety. Anxiety is a condition where a person experiences feelings of anxiety or anxiety and the activity of the autonomic nervous system in responding to an unclear and unspecified threat, and also indicates a state of apprehension or state of worry that complains that something bad is imminent. This can be fatal because the anxious feelings suffered by the individual stem from the loss of meaning in life. So, to overcome the anxiety of death experienced by these individuals, religious counseling is carried out using remembrance. Religious counseling is a help given to a person or a client who has a religious nuance, in order to understand oneself, namely to know oneself, to implement the goals and meaning of life, to form values that hold onto life and to develop as optimal potential as possible. Remembrance is a heart and verbal worship that knows no time limit. Therefore, it needs to be instilled in him to be patient in dealing with it, try to be sincere, carry out worship to the Almighty God so that the anxiety of death will recover. The problem with this research is how to overcome anxiety about death after an accident. The purpose of this study was to determine the anxiety of death after an accident with religious counseling using remembrance. This study uses a qualitative research method that uses a case study approach with the subject of one accident victim aged 21 years. The instrument in this study was observation, interviews and client related data. The results of this mini research study state that religious counseling using remembrance can change anxiety about death after an accident.